The Response of a Structural Target to an Explosive Charge Incorporating Foreign Objects: A Numerical Study - Kang, Gi Ah (Blast Impact and Survivability Research Unit, 2022)
This dissertation reports on the results of a numerical investigation into the effect of incorporating foreign objects into explosive and its subsequent influence on the response of a target structure. The explosive, the container and the ball bearings were simplified representation of the key components of an improvised explosive device (IED). The numerical study was aimed at studying the ball bearing interaction with blast when incorporated into charge, and was based on previous experiments. In the experiments, 22g of plastic explosive charge (26mm in diameter with a length-to-diameter ratio of 1) was detonated inside a fully confined cylindrical mild steel container of 9.3mm wall thickness and 273mm outer diameter. Different experiments were carried out using charges with varying numbers of ball bearings arranged in different configurations. The ball bearings were either packed around the cylindrical charge in row(s), or were randomly embedded into the charge. In the numerical simulations, i) a quarter symmetry model in the radial plane and ii) a half symmetry model in the axial plane were developed in ANSYS AUTODYN using Euler and Lagrangian meshes, based on the previous experiments. The cylindrical target and the ball bearings were modelled using Lagrangian elements, while the air and the PE4 plastic explosive were modelled using Eulerian elements. Ball bearings of fixed diameter 5mm, were placed at positions relative to the charge corresponding to the experimental conditions. The predicted crater depth created in the cylindrical target by ball bearing impact were compared to the experimental results. A comparative numerical study was then conducted to investigate how different factors influenced the ball bearing behaviour and the target response. The parameters tested included the total number and size of ball bearings incorporated in the explosive charge, the manner in which the ball bearings were distributed inside or outside the charge, and the length-to-diameter ratio of explosive used. The numerical models provided insights into how the ball bearing interacted with the blast when incorporated into charge. 2D numerical simulation techniques were used to simulate the velocity distribution of a cased cylindrical explosive charge. The results of the numerical simulations were verified against previously reported equations for fragments and pre-formed fragments, which are based on experimental data which indicated a non-uniform velocity distribution along the cylinder axis. Overall, there was a good agreement between the 2D model and the experimental measurements, including the distribution of the lower velocity values near the cylinder edges. The ball bearing velocity - crater depth correlation was also compared to the projectile velocity equations from literature. A good correlation was shown in all radial simulations. In the axial plane simulations, a good correlation was observed only when the projection angle of the ball bearing was nearly perpendicular to the charge surface. The effect of the ball bearing presence on the overall pressure observed in the confined space is also studied. The inclusion of ball bearings in the charge resulted in an overall decrease in peak pressure, and the percentage decrease was proportional to the total number of ball bearings. Charge covered in rows of ball bearings acted similar to encased charges, especially to charges with pre-fragmented casings. It was observed that an increase in length-to-diameter ratio of the charge led to an overall increase in blast magnitude.